2008
DOI: 10.1177/0886260507309344
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Child Molestation

Abstract: A conceptual model derived from attachment theory was tested by examining adult attachment style, cognitive distortions, and both general and victim empathy in a sample of 61 paroled child molesters and 51 community controls. Results of logistic multiple regression showed that attachment anxiety, cognitive distortions, high general empathy but low victim empathy significantly increased the odds of child molester status. Findings supported theoretically based hypotheses, suggesting that attachment theory may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Indeed, numerous studies have found that individuals who sexually abuse children often exhibit insecure attachment bonds, specifically anxious attachment (Bumby & Hansen, 1997; Lyn & Burton, 2004; Miner et al, 2010; Simons et al, 2008; Smallbone & Dadds, 1998; Ward, Hudson, & Marshall, 1996). Researchers suggest that insecure parent–child attachment can enhance the risk for child sexual offending by creating conditions (e.g., loneliness and isolation, lack of empathy, impulsivity, fear of rejection) that lead some individuals to turn to young children to meet their intimacy needs and desires for interpersonal closeness (see Maniglio, 2012; Smallbone & McCabe, 2003; Wood & Riggs, 2008).…”
Section: Developmental Correlatesmentioning
confidence: 99%
“…Indeed, numerous studies have found that individuals who sexually abuse children often exhibit insecure attachment bonds, specifically anxious attachment (Bumby & Hansen, 1997; Lyn & Burton, 2004; Miner et al, 2010; Simons et al, 2008; Smallbone & Dadds, 1998; Ward, Hudson, & Marshall, 1996). Researchers suggest that insecure parent–child attachment can enhance the risk for child sexual offending by creating conditions (e.g., loneliness and isolation, lack of empathy, impulsivity, fear of rejection) that lead some individuals to turn to young children to meet their intimacy needs and desires for interpersonal closeness (see Maniglio, 2012; Smallbone & McCabe, 2003; Wood & Riggs, 2008).…”
Section: Developmental Correlatesmentioning
confidence: 99%
“…Working within the theoretical framework of attachment, Wood and Riggs (2008) showed that together with anxious attachment and cognitive distortions, high general empathy but low victim empathy may predict child molester status. Puglia et al (2005) found that adult sexual offenders not only preserve an emotional functioning in a normal setting when compared with the general population and to non-sex-offenders, but also are more capable of recognizing emotions.…”
Section: Ei In Sexual Offendersmentioning
confidence: 99%